اتجاهات طلاب اقسام المکتبات والمعلومات بالجامعات المصرية نحو الاختبارات الالکترونية - أحمد شعبان أحمد (المجلة الدولية لعلوم المكتبات والمعلومات)
The current study aimed to measure the attitudes of students of the libraries and information departments in Egyptian universities towards the application of electronic tests, and to discover the differences between male and female attitudes, and students who took computer courses and who did not receive courses towards electronic tests. The researcher relied on the descriptive and analytical method, and the research tool, a questionnaire prepared by the researcher. The study sample reached 311 male and female students. The study indicated that the study sample students enjoy positive trends towards electronic tests, and that there are difficulties facing the application of electronic tests, and demonstrated that there are no differences between male and female attitudes towards electronic tests. The study recommended holding courses in electronic tests for students and faculty members, spreading the culture of applying electronic tests among university students and faculty members